HUKUM MENGGUNAKAN MULTI AKUN UNTUK MENDAPATKAN DISKON PADA E-COMMERCE MENURUT FATWA MUI NO 24 TAHUN 2017 TENTANG HUKUM DAN PEDOMAN BERMUAMALAH MELALUI MEDIA SOSIAL (Studi Kasus Para Pengguna E-Commerce Kota Medan) - Baeha, Tasna Fadhillah (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2023)
Abstract This Journal is titled "The Use of Multiple Accounts to Obtain Discounts on E-Commerce Platforms according to the Fatwa MUI No. 24/2017 (Case Study: E-Commerce Users in Medan City)". This research explores the phenomenon of individuals using multiple accounts to gain larger discounts in online buying and selling transactions. Normatively, this practice is commonly observed in Medan City. The study aims to identify the practice of using multiple accounts to obtain discounts in Medan's e-commerce, analyze the motivating factors behind individuals employing multiple accounts, and evaluate the legal perspective according to the Fatwa MUI No. 24/2017 regarding the use of multiple accounts. The research employs a juridical-empirical approach utilizing case study and statutory analysis methods. Data is collected through interviews, questionnaires, and document analysis. Findings reveal that the practice of using multiple accounts involves altering email addresses or phone numbers. Motivating factors include an interest in online shopping, obtaining cost-effective products, and benefiting from cashback as new users. From an Islamic legal perspective, the use of multiple accounts is governed by the Fatwa MUI No. 24/2017, which mandates transactions through social media to adhere to religious teachings and prohibits elements of Gharar. There's also relevance to Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law).